Penerapan Handover Dalam Mengatasi Manajemen Konflik Untuk Menjaga Patient Safety - Kristina M. Manurung; Novita Asyiah; Veni R. S. Sari; Rika E. Nurhidayah; Husna Sibarani, Inayah (Jurnal Rekam Medis & Manajemen Infomasi Kesehatan, 2023)
In Indonesia, conflict management has received less attention from organizations and governmentagencies who view conflict as bad and destructive. This begins, for example, in lessons and trainingthat is taught that life is something that is harmonious, harmonious and balanced. Handover is a wayto convey information to caregivers when changing production shifts. more easily handled by nurseup-to-date information about the patient's condition. The research objective was to determine theapplication of shift change in overcoming nurse conflict management. The research method in thisstudy was to use a literature review. Patient safety is an important element of the quality of healthservices that must be considered in all health services. The results of this study indicate that theweighing and receiving procedure is more effective in improving continuity, quality and safetybetween nurses and patients in providing quality services to patients.